A humanoid robotics simulation and control platform for NINO. (2016) - Hsu, Huan-Kun; Huang, Han-Pang; Lo, Sheng-Yen
The recent increase in technological maturity has allowed humanoid robots to interact with humans in real-world applications. A simulator of humanoid robots with the characteristics of digital human models plays a significant role for humanoid motion planning in those complex environments. In this paper, a humanoid robotics simulation and control platform is proposed for the developed humanoid robot, NINO. The platform consists of a simulator, the visualisation tool, motion planning algorithms, and a motion control library. It can simulate realistic physical interactions between the robot and its environment during locomotion and keep consistent performance between the simulator and the actual humanoid robot. The simulator can control both the virtual and physical robots. The performance and applications of the simulator platform have been justified through the simulation results of several biped locomotion tasks.